2020
DOI: 10.21037/qims-20-742
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced near-infrared spectroscopy using indocyanine green on moderate and severe traumatic brain injury: a prospective observational study

Abstract: Background: The care given to moderate and severe traumatic brain injury (TBI) patients may be hampered by the inability to tailor their treatments according to their neurological status. Contrast-enhanced near-infrared spectroscopy (NIRS) with indocyanine green (ICG) could be a suitable neuromonitoring tool.Methods: Monitoring the effective attenuation coefficients (EAC), we compared the ICG kinetics between five TBI and five extracranial trauma patients, following a venous-injection of 5 mL of 1 mg/mL ICG, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…Such pathologies include but are not limited to Alzheimer’s, 1 Parkinson’s, 2 epilepsy, 3 and traumatic brain injury. 4 , 5 Psychiatric conditions such as schizophrenia 6 and anxiety 7 have also been studied, demonstrating the benefit of this technique over conventional technologies such as fMRI, PET, and EEG. The basic principle behind fNIRS is that different constituents in biological tissue absorb and scatter near-infrared (NIR) wavelengths of light (typically 650 to 950 nm) to a varying degree based on their extinction coefficient, cellular size, and density.…”
Section: Introductionmentioning
confidence: 99%
“…Such pathologies include but are not limited to Alzheimer’s, 1 Parkinson’s, 2 epilepsy, 3 and traumatic brain injury. 4 , 5 Psychiatric conditions such as schizophrenia 6 and anxiety 7 have also been studied, demonstrating the benefit of this technique over conventional technologies such as fMRI, PET, and EEG. The basic principle behind fNIRS is that different constituents in biological tissue absorb and scatter near-infrared (NIR) wavelengths of light (typically 650 to 950 nm) to a varying degree based on their extinction coefficient, cellular size, and density.…”
Section: Introductionmentioning
confidence: 99%
“…The application of NIRS in a clinical context can be hampered by multiple elements that affect the quality of the data recorded: sweat, which affects the probe–skin coupling; motion artifacts, due to involuntary movements under light sedation; ambient light–noise; poor feedback on the quality of the signal acquired during the acquisition; etc. [ 7 , 120 , 121 ].…”
Section: Intracranial Tissue Partial Oxygen Pressure and Near-infrmentioning
confidence: 99%
“…The passage of a bolus of contrast dye (i.e., ICG) through the brain can be monitored using NIRS [ 120 , 144 ]. The kinetic of the ICG can be related to cerebral perfusion and BBB integrity [ 120 , 144 ].…”
Section: Future Application Of Tissue Partial Oxygen Pressure and mentioning
confidence: 99%
“…This can be explained by an impairment in cerebral autoregulation, which saw the increasing ICP cause cerebral hypoperfusion (19,20) leading to a decrease in cerebral blood volume (21) brain cells require oxygen to metabolize, the more deoxyhemoglobin is produced. Forcione et al have nicely shown how this can be done with dynamic contrast-enhanced NIRS with indocyanine green in TBI patients (25,26).…”
Section: The Changes In Relative Concentrations Ofmentioning
confidence: 99%